Overview of Sales And Investment of Hard Drugs in Pharmacy “X” In Pamusian Village, Tarakan City With ABC Analysis For The Period Of October 2023 – October 2024 - Iqradiya, Azdyra; Heriani; Sari Wijayanti (Jurnal FARMASIMED (JFM), 2025)
Background: This study aims to evaluate the sales and investment of hard drugs at Pharmacy "X" Pamusian Village, Tarakan City, using the ABC analysis method during the period from October 2023 to October 2024. Objectives: The ABC analysis method is applied to group drugs into three categories based on investment value and contribution to sales. Research method: The data analyzed include sales of hard drugs, investment value, and pharmacology categories. Results: The results of the study show that out of a total of 169 hard drug items, group A consists of 48 items with the highest investment value, group B includes 45 items with moderate contributions, and group C consists of 76 items with the lowest investment value. This grouping provides guidance for pharmacies in managing stock and investment more efficiently to meet market needs. Conclusion: In conclusion, the ABC analysis method helps Pharmacy "X" in prioritizing capital management and increasing operational efficiency by focusing on drug groups that have the greatest impact on sales.